Push-out bond strength of fiberglass posts cemented with adhesive and self-adhesive resin cements according to the root canal surface - Pereira, Jefferson Ricardo; Pamato, Saulo; Santini, Manuela Favarin; Porto, Vinicius Carvalho; Ricci, Weber Adad [UNESP]; Reis So, Marcus Vinicius (Elsevier B.V., 2021)
Objective: Evaluating the bond strength of fiberglass posts cemented with different resin cements.Materials and Methods: Seventy freshly extracted roots of healthy human canines were endodontically treated and prepared to receive fiberglass posts. The roots were randomly divided into seven groups: (G1) RelyX ARC, (G2) Enforce, (G3) BisCem, (G4) Duo-Link, (G5) Cement Post, (G6) Variolink II, and (G7) RelyX U200. After post cementation, the specimens were sectioned perpendicularly to the root axis using a high-speed diamond disc, totaling 340 specimens. The strength values obtained in the push-out test were submitted to two-factor ANOVA and Tukey test (p = 0.05). Results: The root thirds (p = 0.001) and the type of cement (p = 0.001) influenced the bond strength values. The relation between these two factors was also significant (p = 0.011). Conclusions: The bond strength of self-adhesive resin cements was significantly higher as compared to other cements. Besides the cervical third in roots cemented with conventional cements types presented the highest bond strength values (p < 0.05). (C) 2019 The Authors. Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Bond strength; Resin cement; Self-adhesive; Fiberglass post; Dentin surface